Flower composition of black pepper (Piper nigrum L.) varieties in Bintulu, Sarawak - S., Noorasmah; J., Nurul A'in; D. R., Shiamala (Malaysian Society of Plant Physiology, 2019)
This paper presents the results of studies conducted to evaluate the morphology of black pepper (Piper nigrum) flowers in Bintulu (Sarawak, Malaysia), identify the shading effect on pepper productivity of the Kuching, Semongok Aman and Semongok Emas cultivars and identify the composition of flowers on the spikes of the different cultivars. It was shown that light intensity, as represented in the different canopy levels of the vines, appeared to be conversely related to the production of black pepper. The canopy levels did not significantly affect the peduncle and spike length of the black pepper cultivars.